Developing a bi-objective location-allocation-inventory problem for humanitarian relief logistics considering maximum allowed distances limitations. (9th December 2020) - Cheraghalipour, Armin; Farsad, Saba; Paydar, Mohammad Mahdi
The crises are the inevitable realities of human life, which occur naturally or by mankind suddenly and require urgent and fundamental measures to resolve it. In this research, a linear bi-objective mathematical model for the preparation phase of crisis management is formulated. The proposed model studies location-allocation problem with multiple commodities and attempts to minimise total costs along with maximising the minimum weight of constructed locations. Moreover, the maximum allowed distances for damaged areas from main roads and equipped hospitals as novel limitations are considered. Also, the model is verified by some applied examples and to solve it, some of the well-known multi-objective decision making (MODM) approaches includes weighted sum method, LP-metric method, and goal programming technique are used. Moreover, in order to measure efficiency of the proposed model, a sensitivity analysis is performed, which finally, the best constructed locations with minimum weights and costs are selected. The obtained results can be useful for crisis organisation.